Effect of dopant-induced local vibration modes on pressure-driven structural phase transition in Mn- and Co-doped ZnO - Chih-Ming Lin; Yi-Jia Tsai; Yi-Sheng Huang; Chia-Hung Hsu; Bo-Shiuan Chen; Ming-Fong Tai; Sheng-Rui Jian; Jenh-Yih Juang (iScience)
Summary: In-situ laser Raman spectroscopy was performed on pristine ZnO, Zn0.98Mn0.02O, and Zn0.98Co0.02O at pressures up to 18.6, 18.4, and 13.1 GPa, respectively, to explore how minute amount of Mn- and Co-doping affects the high-pressure wurtzite-to-rocksalt transition in ZnO. Pristine ZnO exhibited characteristic wurtzite phonon modes, whereas Mn- and Co-doping introduced distinct local vibrational modes that shifted differently under compression. These shifts revealed that Zn0.98Mn0.02O undergoes a unique phase transition path compared to pristine and Co-doped ZnO. By connecting local vibrational features to structural evolution at high pressures, this study demonstrates the capability of Raman spectroscopy to detect doping-induced changes in lattice dynamics. These insights advance our understanding of how local lattice effects influence phase transitions and guide the design of ZnO-based materials with tunable properties for optoelectronic and high-pressure applications.